Topographic And Anatomical Pathways Of Tumor Dissemination In The Female Reproductive Organs (Texas Journal of Medical Science, 2026)
The anatomy of the female pelvis and reproductive organs constitutes a highly complex topographic– anatomical system that plays a pivotal role in understanding the clinical behavior and dissemination patterns of malignant tumors. Accurate knowledge of pelvic anatomy is of particular importance in gynecologic oncology, where surgical strategy, the extent of lymphadenectomy, identification of metastatic routes, and prognostic assessment are directly influenced by individual variations in vascular supply, lymphatic drainage, organ syntopy, and fascial and cellular compartments. Although classical anatomical descriptions of the pelvic organs are well established, contemporary evidence derived from magnetic resonance imaging, computed tomography, three-dimensional reconstruction, and lymphatic mapping has revealed substantial interindividual anatomical variability. These findings necessitate a critical reappraisal of traditional concepts regarding tumor spread, especially in cervical cancer, endometrial carcinoma, and ovarian neoplasms. The present review aims to synthesize current data on the anatomy of the female pelvis, fascial planes, cellular spaces, and lymphatic pathways, as well as to elucidate their role in the dissemination of gynecologic malignancies and their implications for surgical management.